Labour market institutions and their effects on labour market performance in the new EU member countries - Fialová, Kamila; Schneider, Ondrej (Munich, 2008)
"This article focuses on the role of labour market institutions in explaining different labour market developments in European countries, with a special attention to the new European Union member countries. This may allow us to analyse effects of various institutional setups and of their changes on major labour market indicators. We aim at complementing several studies from the late 1990’s by using more recent data that allow us to compare institutional setups from the mid 1990’s and early 2000’s both in “old” and “new” EU member states. We estimate effects of labour market institutions on various performance indicators (unemployment, long-term unemployment, employment, activity rate). Our results confirm that high taxes increase unemployment, while active labour market policies tend to reduce it. We also show that stricter employment protection, higher taxes and larger economic burden represented by the minimum wage decrease employment and activity rate. Moreover, statistical tests indicate that there is a difference in the institutional effects between “old” and “new” EU members. "